Persepsi Mahasiswa Pada Pelaksanaan Program Merdeka Belajar Kampus Merdeka (MBKM) Di Program Studi Pendidikan Sejarah Fkip Univeristas Tanjungpura - Refti Yusli Ananda; Ika Rahmatika Chalimi; Haris Firmansyah (Journal on Education, 2025)
This study investigates student perceptions of the Merdeka Belajar Kampus Merdeka (MBKM) program within the History Education Study Program at FKIP Tanjungpura University. Using a qualitative case study, the research gathered data through observation, interviews, and document analysis from the MBKM head, lecturers, and History Education students who had participated or were currently participating in the program. Data were analyzed through reduction, presentation, and verification. The findings reveal that the History Education program has implemented six MBKM initiatives since 2022: agency internships, MSIB, PMM, the Merdeka Entrepreneurial Program, Teaching Assistance, and Teaching Campus, with implementation involving registration, document collection, and graduation announcements. Student perceptions were mixed, with some expressing joy at gaining firsthand work experience, while others felt confusion and faced difficulties with procedures, placement, and work program design. Ultimately, students gained valuable direct field experience through the MBKM program